2020
DOI: 10.1177/1754337120917809
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface roughness on oblique bicycle helmet impact tests

Abstract: The friction between a helmet and impact surface affects the accelerations imparted to the head. The roughness of the impact surface is, therefore, a consideration when developing oblique impact standards. An 80-grit abrasive paper is commonly used in oblique impact tests to simulate a road surface, but has not been validated for bicycle impacts and may not accurately represent real road surfaces. In the following study, a helmeted NOCSAE headform with a Hybrid III neck was dropped onto a 45° anvil at 6.5 m/s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In helmet testing, the coefficient of friction of the anvil has been found to significantly affect the helmet kinematics, in particular rotational motion. 92 Current helmet standard and rating methods which include oblique impacts commonly use oblique anvil covered with 80-grid abrasive paper. This anvil condition represents an upper bound of the coefficient of friction.…”
Section: Impact Surfacementioning
confidence: 99%
“…In helmet testing, the coefficient of friction of the anvil has been found to significantly affect the helmet kinematics, in particular rotational motion. 92 Current helmet standard and rating methods which include oblique impacts commonly use oblique anvil covered with 80-grid abrasive paper. This anvil condition represents an upper bound of the coefficient of friction.…”
Section: Impact Surfacementioning
confidence: 99%
“…Composite materials, such as carbon fibre reinforcement, were evaluated as an alternative material of the helmet shell with good penetration resistance and ability of absorbing impact energy [20,21]. Besides, Finan et al [22] and Petersen et al [23] reported that the friction coefficient between the helmet and the obstacle had some influence on the head rotational acceleration in the oblique impact, but the influence in the normal impact seemed relatively small. Other conditions, such as impact velocity, impact angle and strap tension, are also considered in the impact between a helmet and an obstacle.…”
Section: Introductionmentioning
confidence: 99%
“…B95) and American Society for Testing and Materials (ASTM F1447) ( Commision, 1998 ; Hansen et al, 2013 ; McIntosh et al, 2013 ). In these tests, helmets are placed on a headform and dropped onto a steel anvil coated with adhesive-backed 80-grit paper ( Commision, 1998 ; Hansen et al, 2013 ; McIntosh et al, 2013 ; Bland, 2019 ; Bliven et al, 2019 ; Petersen et al, 2020 ). The head kinematics during the drop tests are then measured using accelerometers and gyroscopes, which are attached at the center of gravity of the headforms.…”
Section: Introductionmentioning
confidence: 99%